EVALUASI BRANDING JOGJA NEVER ENDING ASIA SEBAGAI STRATEGI MEMASARKAN DAERAH DI ERA OTONOMI - , Ekklesia Hendra Pratama, SIP ([Yogyakarta] : Universitas Gadjah Mada, 2011)
A very hard and complicated competition in the era of globalization today urged every country should develop innovation and creativity that is not left with any other country. Yogyakarta, for example, are no longer competing only with Bali, Bandung or Jakarta, but also at the same time compete with the Kuala Lumpur, Phuket, or Singapore. Realizing this, Yogyakarta had risen by marketing place. Through the brand image of "Jogja Never Ending Asia" is an attempt Yogyakarta participate in global competition. This study aims to determine the factors underlying the birth of branding "Jogja Never Ending Asia, the reason for choosing the phrase" Jogja Never Ending Asia "as a brand DIY, why brand is not implemented properly, and to determine the respondent's perception about the brand. Theoretically, this study describes is only fitting that each region has a strong concept. This concept is a "spirit" or blueprint that fosters the development or marketing areas. The concept is starting to lead the formation of regional branding. This type of research is a descriptive study using survey methods, with techniques of data collection questionnaire, interview, observation and documentation. Determination of research informants using purposive sampling method, a person involved in the process of branding the birth of Jogja Never Ending Asia, such as former board IMA Chapter DIY, and DIY and former Secretary of State, then followed by snowball sampling to a few parties that are considered to have the information and knowledge relevant about branding Jogja Never Ending Asia. While respondents in the study were as many as 100 respondents consisting of elements of the business, community, students, tourists, foreign tourists, and was chosen as a sample by simple random sampling methods. From the research results can be seen that the economic crisis Indonesia, decentralization, and globalization is a factor underlying the birth of the brand. The reason the phrase Jogja Never Ending Asia was chosen as a branding DIY, is a cultural reasons, the community of global markets and global competition. Branding is not implemented properly because of ineffective socialization, and the lack of participation and coordination in the birth process and implementation of branding. Respondents are still many who do not know the brand and its meaning. Many people only use the logo without the inclusion is accompanied by Never Ending Asia. In essence, brand Jogja Never Ending Asia are still considered relevant because of the Long-Term Regional Development Plan (RPJPD) Special Region of Yogyakarta Province has established Regional Development Vision to be achieved in the year 2025, which became prominent in Southeast Asia in the field of Education, Culture and Tourism Destination .